Heteropoda dagmarae sp. nov. from Laos—a close relative of Heteropoda javana (Simon 1880) from Indonesia (Arachnida: Araneae: Sparassidae) - Jäger, Peter; Vedel, Vincent (Zootaxa, 2005)
A new species of Heteropodinae is described from northern Laos: Heteropoda dagmarae sp. nov. From genital as well as somatic characters it seems to be closely related to Heteropoda javana (Simon 1880) from Sumatra and Java. A javana species-group is proposed within Heteropoda Latreille 1804 by means of these two species and several undescribed species.